2004
DOI: 10.1111/j.1075-122x.2004.21336.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Granulomatous Mastitis: Time to Avoid Unnecessary Mastectomies

Abstract: Idiopathic granulomatous mastitis is a rare disease of the breast. Clinically and radiologically it may mimic breast carcinoma. Awareness of surgeons, pathologists, and radiologists is essential to avoid unnecessary mastectomies. Data regarding 24 patients with histologically confirmed idiopathic granulomatous mastitis treated at our center over 8 years were analyzed. The mean age of patients was 34.3 years. Breast lump was the most common presentation. The right breast was affected in 16 cases. Four patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
309
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(330 citation statements)
references
References 26 publications
9
309
1
11
Order By: Relevance
“…In some cases, breast abscess, fibroses and fat necrosis can occur. Reactive axillary lymphadenopathy may also be presented, as in our case report 1,5,8,10,11 . Histology is characterized by a non-caseating granulomatous inflammatory response of the breast lobules in the absence of specific underlying causes.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In some cases, breast abscess, fibroses and fat necrosis can occur. Reactive axillary lymphadenopathy may also be presented, as in our case report 1,5,8,10,11 . Histology is characterized by a non-caseating granulomatous inflammatory response of the breast lobules in the absence of specific underlying causes.…”
Section: Discussionmentioning
confidence: 51%
“…The MRI can include a parenchymal asymmetry or distortion with different contrast enhancement patterns (diffuse, heterogeneous and ring-shaped enhancement). In our case, the MRI showed a regional enhancement, and because there were other signs in the skin and lymph nodes, an inflammatory process was suggested 1,4,10 . Although radiology findings have a limited value, our report showed that they can be used to monitor the clinical response in a conservative treatment 13 .…”
Section: Discussionmentioning
confidence: 56%
“…Mammographic features of IGM are essentially nonspecific, with focal asymmetric density being the most common feature. [7][8][9][10][11] Our study showed that the most common radiological findings observed were dilated ducts with inflammatory changes, with some patients (15%) showing cystic lesions with thick debris. Using mammography, 20% of our patients displayed asymmetric diffuse density of fibroglandular tissue and with ultrasound, 20% of the patients showed hypoechoic ill-defined lesions.…”
Section: Discussionmentioning
confidence: 59%
“…Clinically and radiologically, it mimics carcinoma of the breast. The most common complaints of patients are unilaterally emerging breast pain or painless masses (2,3). This case highlights the possibility that the concurrence of chronic granulomatous mastitis with breast cancer may be explained just as an adjunct situation or a coincidence and may be the difficulty in distinguishing one from the other.…”
Section: Introductionmentioning
confidence: 90%